2012
DOI: 10.1111/j.1438-8677.2012.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking altitudinal gradients and temperature responses of plant phenology in the Bavarian Alps

Abstract: Global climate change influences ecosystems across the world. Alpine plant communities have already experienced serious impacts, and will continue to do so as climate change continues. The aim of our study was to determine the sensitivity of woody and herbaceous species to shifts in temperature along an altitudinal gradient. Since 1994, park rangers have been making phenological observations at 24 sites from 680 to 1425 m a.s.l. Each year 21 plant species were observed once or twice weekly from March to July; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 53 publications
7
46
2
2
Order By: Relevance
“…Also, Cornelius, Estrella, et al. (2013) detected differences in phenological responses between observational sites in the Alps. Hopkins law states that species should delay their phenology by 3.3 day 100/m (Fitzjarrald, Acevedo, & Moore, 2001; Vitasse, Delzon, et al., 2009) yet only three species reacted almost as strongly as predicted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Cornelius, Estrella, et al. (2013) detected differences in phenological responses between observational sites in the Alps. Hopkins law states that species should delay their phenology by 3.3 day 100/m (Fitzjarrald, Acevedo, & Moore, 2001; Vitasse, Delzon, et al., 2009) yet only three species reacted almost as strongly as predicted.…”
Section: Discussionmentioning
confidence: 99%
“…C. defloratus shifted its phenology by 3.28 day 100/m, P. orbiculare by 3.26 day 100/m, and T. pratense by 3.06 day 100/m, the other species were less responsive. Other observational studies in alpine grasslands showed an average delay of 3.8 day 100/m (Cornelius, Estrella, et al., 2013; Cornelius, Leingärtner, et al., 2013). Interestingly, for A. foetida and M. perennis, the reaction was much less pronounced compared to the observations on these species reported by Cornelius, Estrella, et al., 2013 and Cornelius, Leingärtner, et al., 2013; 2.19 day 100/m instead of 3.7 day 100/m for A. foetida and 0.85 day 100/m compared to 3.5 day 100/m for M. perennis , respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the mean GP-SOS and its trends, the early detecting LSP-SOS in form of 20% amplitude and 3rd derivative were also able to capture the high inter-annual variability of early species GP-SOS (understory) occurring before 90th day of the year (Supplementary Figure S6). These early species are limited by the frost period and hence show higher response to temperature fluctuations and therefore a higher inter-annual variability in their SOS [45,46]. The lower correlations of early understory species' GP-SOS with LSP-SOS could be due to the short time series of data or may be due to artefacts introduced in smoothing of early season NDVI.…”
Section: Inter-and Intra-annual Variability In Lsp-and Gp-sosmentioning
confidence: 99%
“…La variabilidad ambiental se relaciona con factores tales como la radiación solar, la temperatura del aire, las propiedades del suelo y el défi cit hídrico (Molina-Montenegro, 2008; Molina-Montenegro y Cavieres, 2010;Cornelius et al, 2013). En consecuencia, las plantas modulan 19° 26' 55.4" 98° 46' 39.3" 2 3,366 19° 26' 16.2" 98° 45'10.0" 3 3,386 19° 26' 19.0" 98° 44' 55.9" 4 3,545 19° 24' 43.3" 98° 44' 59.3" Cuadro 1.…”
unclassified